The History of Islamic Kingdoms in Kapuas Hulu District: A Manuscript Translation of Pangeran Kesoema Anom Soeria Negara - Bibi Suprianto; Zaenuddin Hudi Prasojo; Doli Witro (Center for Research and Development of Religious Literature and Heritage, 2021)
Kapuas Hulu is an area located in the interior of West Kalimantan and has 23 sub-districts well-known for their ethnicity, race and culture. Kapuas Hulu has also small kingdoms originating from the Sintang region. The Muslims in Kapuas Hulu come from Dayak tribe, who later converted to Islam. The sultanate’s presence played an important and strategic role, even determined the development of Islam itself in the territory. At the same time, there were some obstacles to Islamization throughout the coastal Sultanate which caused “Near Pedalaman“ area a bit late in accepting Islam. This article discusses the history of the Islamic kingdom in Kapuas Hulu Regency, which is examined from the translation of the manuscript of Prince Kesoema Anom Soeria Negara. This paper traces the development of Islam and the rulers of Islamic kingdoms in Kapuas Hulu Regency. This article is qualitative research. After the data was collected with heuristics, it was analyzed by source criticism, interpretation, and historiography. Study results demonstrate that the kingdoms in Kapuas Hulu have contributed to leading their respective villages and providing a solid cultural system for maintaining cultural and state assets. Thus, many local residents converted to Islam through the royal system. Kiyai Pati Uda was the first king from Jongkong sub-district. Another finding indicates that the Prince Kesoema Anom Soeria Negara manuscript also includes the names of royal descendants from Kapuas Hulu Regency, namely from Jongkong, Nanga Suhaid, Bunut, and other sub-districts.